Neoliberal multiculturalism and the discourse of primitivism at Walt Disney World's Pandora. Issue 3 (3rd July 2019) - Roderick, Ian
ABSTRACT: Taking a Multimodal Critical Discourse Analysis approach, this paper examines the myriad ways in which the Walt Disney World attraction, Pandora – The World of Avatar, exemplifies neoliberal multiculturalism. The different signifying elements and the manner in which they are being put to use are initially described to account for their affordances and the discourses they index. Particular attention is given to the use of materials, texture, and colours and the ways that they represent the ecology of Pandora, the past mining, and the current conservation activities. Having described the chosen semiotic materials, the representation of the Na'vi in relation to the discourses of primitivism, progress and sublimity is then analysed. Constituted as noble savages, it is argued that the Na'vi are both held up as an ideal, untainted by the corruption of the modern world, and at the same time rejected as monocultural Others who have failed to progress.